2019
DOI: 10.2139/ssrn.3477066
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Barriers to Adoption of ‘No-Cost’ Greenhouse Gas Mitigation Practices in Pastoral Systems

Abstract: Gases. The authors wish to thank all the interviewees for their time, insights, and knowledge shared. Without their contributions this paper would not have been possible. This paper has greatly benefitted from comments from Cecile de Klein, Robyn Dimes, Joorie Knook and Shaan Badenhorst. Our thanks for their review. Disclaimer The authors are responsible for all opinions expressed and any errors or omissions. Human ethics approval was granted by AgResearch. In addition, human ethics approval was given by the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Considerable effort has been made by both the public and private sector to determine climate change mitigation solutions in NZ, and central to this is to reduce the GHGs emissions caused by agricultural production [128]. For instance, in the agricultural sector it is suggested that changes to land use and pasture management will be key solutions for reducing GHGs emissions along with other strategies (e.g., innovation in animal genetics and breeding) [129]. It is therefore suggested that multiple land use options (e.g., pasture, forestry, horticulture) need to be considered in relevant areas of the hill country and the integration of climate change scenarios needs to be made into future land use plans for more comprehensive land use planning and management models capable of addressing issues related to climate change.…”
Section: Introduction To New Zealand Hill Country and Its Environmnet...mentioning
confidence: 99%
“…Considerable effort has been made by both the public and private sector to determine climate change mitigation solutions in NZ, and central to this is to reduce the GHGs emissions caused by agricultural production [128]. For instance, in the agricultural sector it is suggested that changes to land use and pasture management will be key solutions for reducing GHGs emissions along with other strategies (e.g., innovation in animal genetics and breeding) [129]. It is therefore suggested that multiple land use options (e.g., pasture, forestry, horticulture) need to be considered in relevant areas of the hill country and the integration of climate change scenarios needs to be made into future land use plans for more comprehensive land use planning and management models capable of addressing issues related to climate change.…”
Section: Introduction To New Zealand Hill Country and Its Environmnet...mentioning
confidence: 99%